Active play for special needs: The impact of running and jumping games on motor skills in children with intellectual disabilities - Raharjo, Slamet; Yunus, Mahmud; Andiana, Olivia; Subagio, Irmantara (Universitas Tanjungpura, 2025)
Background. Children with intellectual disabilities generally experience impairments in motor skills, movement coordination, physical health, and environmental awareness. Therefore, effective play-based therapy to improve motor impairments in children with intellectual disabilities is highly needed. Objectives. This study aims to examine the effect of a running and jumping game model in improving motor impairments in children with intellectual disabilities. Methods. This study used a pre-experimental design involving male children with intellectual disabilities aged 11